Analysis of Risk Factors of Neonatal Asphyxia in Labuang Baji Hospital, Makassar, 2021 - Shanun Shari Sakunti,; Rini Fitriani,; Syatirah Jalaluddin,; Andi Tihardimanto , (Alami Journal (Alauddin Islamic Medical) Journal, 2024)
Analysis of Risk Factors of Neonatal Asphyxia in Labuang Baji Hospital, Makassar, 2021. Asphyxia was the second leading cause of neonatal death in Indonesia in 2019, with 5,464 cases reported. Asphyxia occurs due to inadequate blood flow or gas exchange to or from the fetus in newborns. If not promptly and adequately addressed, this condition can damage vital organs. This study aims to identify the risk factors influencing the incidence of neonatal asphyxia at RSUD Labuang Baji Makassar. The research design employed is an observational analytic approach with a case-control method. Sampling was conducted using purposive sampling techniques with secondary data from patient medical records. The sample consisted of 47 cases and 47 controls, and analysis was performed using chi-square tests and odds ratios. The study found a p-value <0.05 for the association between asphyxia and maternal anemia, premature rupture of membranes (PROM), and low birth weight (LBW), with odds ratios of 3.410, 3.872, 7.451, and 7.765, respectively. The p-value >0.05 indicated no significant association between asphyxia and maternal age, preeclampsia, parity, and mode of delivery. This study concludes that maternal anemia, premature rupture of membranes (PROM), low birth weight (LBW), and gestational age are risk factors for neonatal asphyxia at RSUD Labuang Baji Makassar in 2021.